Supernova 2018cuf: A Type IIP Supernova with a Slow Fall from Plateau - Dong, Yize (2021)
We present multiband photometry and spectroscopy of SN 2018cuf, a Type IIP (“P” for plateau) supernova (SN) discovered by the Distance Less Than 40 Mpc Survey within 24 hr of explosion. SN 2018cuf appears to be a typical SN IIP, with an absolute V-band magnitude of −16.73 ± 0.32 at maximum and a decline rate of 0.21 ± 0.05 mag/50 days during the plateau phase. The distance of the object was constrained to be 41.8 ± 5.7 Mpc by using the expanding photosphere method. We used spectroscopic and photometric observations from the first year after the explosion to constrain the progenitor of SN 2018cuf using both hydrodynamic light-curve modeling and late-time spectroscopic modeling. The progenitor of SN 2018cuf was most likely a red supergiant of about 14.5 M⊙ that produced 0.04 ± 0.01 M⊙ ⁵⁶Ni during the explosion. We also found ∼0.07 M⊙ of circumstellar material (CSM) around the progenitor is needed to fit the early light curves, where the CSM may originate from presupernova outbursts. During the plateau phase, high-velocity features at ∼11,000 km s⁻¹ were detected in both the optical and near-infrared spectra, supporting the possibility that the ejecta were interacting with some CSM. A very shallow slope during the postplateau phase was also observed, and it is likely due to a low degree of nickel mixing or the relatively high nickel mass in the SN.